Differences in Some Morphological Characteristics between Students of Younger School Age from Niksic and Mojkovac - Boris Banjevic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
Kinesiologists have long ago noticed the great importance of determining and comparing parameters of growth and development in certain age of school children and youth. The aim of the research is to determine eventual existence of statistically significant differences in morphological characteristics between students younger school age from Niksic (Central region of Montenegro) and Mojkovac (Northern region of Montenegro). The research has been performed on a sample of 101 students divided into two groups: 60 students from the second and and third grade of the Primary school "Jagos Kontic" from Niksic and 41 students from the second and and third grade of the Primary school "Aleksa Djilas Beco" from Mojkovac. Morphological characteristics were evaluated by a battery of four variables: body height, body weight, waist circumference and hip circumference. The significance of the differences between students from Niksic and Mojkovac was determinated by t-test for small independent samples. Statistically significant differences in favor of students from Mojkovac have been established in certain morphological parameters. The obtained results of research confirm the need to perform a more comprehensive research based on the comparision of the morphological indicators of students from different parts of Montenegro.